2021
DOI: 10.1182/bloodadvances.2021005148
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic enrollment disparities and demographic reporting requirements in acute leukemia clinical trials

Abstract: Data regarding racial and ethnic enrollment diversity for acute myeloid (AML) and lymphoid leukemia (ALL) clinical trials in the United States (US) are limited, and little is known about the effect of federal reporting requirements instituted in the late 2000s. We examined demographic data reporting and enrollment diversity for US ALL and AML trials from 2002-2017 as well as changes in reporting and diversity after reporting requirements were instituted. Of 223 AML and 97 ALL trials with results, 68 (30.5%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
2
13
1
Order By: Relevance
“…Disappointingly, when compared with the high proportion of Hispanic AYA ALL patients across the United States, we found that Hispanic AYAs were under-represented on CALGB 10403. While this is in keeping with other reports showing disparities in clinical trial enrollments among Hispanic patients, 16,22 - 25 we were able to demonstrate that under-enrollment was in part due to a misalignment between the geographical distribution of enrollees and the distribution of Hispanic AYA ALL patients across the United States. These findings imply that strategies to improve clinical trial enrollment among Hispanic ALL patients should include efforts to more closely align study sites and accrual projections with disease incidence patterns.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Disappointingly, when compared with the high proportion of Hispanic AYA ALL patients across the United States, we found that Hispanic AYAs were under-represented on CALGB 10403. While this is in keeping with other reports showing disparities in clinical trial enrollments among Hispanic patients, 16,22 - 25 we were able to demonstrate that under-enrollment was in part due to a misalignment between the geographical distribution of enrollees and the distribution of Hispanic AYA ALL patients across the United States. These findings imply that strategies to improve clinical trial enrollment among Hispanic ALL patients should include efforts to more closely align study sites and accrual projections with disease incidence patterns.…”
Section: Discussionsupporting
confidence: 91%
“…This survival disparity may be partially explained by recent evidence that ALL in patients of Hispanic ethnicity is more likely to harbor high-risk Philadelphia chromosome (Ph)-like aberrations, including gene translocations involving CRLF2 , 8,9 IKZF1 deletions, and germline polymorphisms in GATA3 . 10,11 Additional challenges disproportionately affecting Hispanic patients, such as lower socioeconomic status, 12 reduced medication adherence, 13 higher rates of obesity, 14 altered drug metabolism, 15 and low rates of clinical trial enrollment 16 also likely contribute.…”
Section: Introductionmentioning
confidence: 99%
“…22.00307 because of lower prevalence. 4,15,16 Our ClinicalTrials.gov national trial analysis found that Black, Native American, Asian, and Hispanic adults with acute leukemia were underenrolled by 51%, 56%, 36%, and 48%, respectively, 13 but data sources limited patient-or site-level assessment.…”
Section: Introductionmentioning
confidence: 99%
“…1,13 The presence, degree, and reasons for under-representation vary by cancer and trial type. 13,14 Adult acute myeloid (AML) and lymphoblastic leukemia (ALL) are aggressive but curable blood cancers with distinctive care needs that make trial enrollment processes unique: patients require therapy within days of diagnosis, treatment is frequently inpatient, substantial proportions are treated and enrolled at National Cancer Institute (NCI) Comprehensive Cancer Centers (CCCs), and reliance on multicenter studies is higher…”
Section: Introductionmentioning
confidence: 99%
“…Despite optimism, ALL in adults remains a lethal disease. Ongoing trials, with representation of all racial, ethnic, and socioeconomic groups, 110 are needed to make even further dramatic improvements. This is an exciting time for adult ALL, but the best is yet to come!…”
Section: Discussionmentioning
confidence: 99%